1999
DOI: 10.1007/s004390051100
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between clinical phenotype, semen parameters and aneuploidy frequency in sperm nuclei of 50 infertile males

Abstract: The purpose of this study was to analyse the frequency of disomy for chromosomes 1, 13, 14, 18, 21, 22, X and Y in sperm nuclei of 50 infertile men and 10 healthy probands of proven fertility. Semen parameters (sperm count, global motility and morphology), urological clinical examination, genital ultrasound and lymphocyte karyotyping were performed for each patient. Disomy frequency was established by fluorescence in situ hybridization by using whole chromosome paint probes. The mean rate of disomy for the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
54
3
10

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 29 publications
13
54
3
10
Order By: Relevance
“…Our data are in discordance with the data found by Morel et al [20] and Rives et al [21]. Indeed, Morel et al [20] have conducted a study on human semen samples randomly selected from a population of men undergoing an infertility work up and did not established a correlation between subject age and disomy frequencies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our data are in discordance with the data found by Morel et al [20] and Rives et al [21]. Indeed, Morel et al [20] have conducted a study on human semen samples randomly selected from a population of men undergoing an infertility work up and did not established a correlation between subject age and disomy frequencies.…”
Section: Discussioncontrasting
confidence: 99%
“…As shown in our study, inverse relationships between sperm concentration and the mean frequency of disomy of sex chromosome and diploidy were found. Our results are in accordance with the data of many other studies that reported significant negative correlations between sperm concentration and the mean frequency of disomy, especially for the sex chromosomes [6,10,15,21,22]. However, other studies did not show a significant correlation between sex disomy rates and sperm concentration [3,20,23,24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Most carriers of Robertsonian translocations have oligozoospermia. This may be a result others either did not show it [7,24,25] or attributed the increased aneuploidy rate due to the oligoasthenoteratozoospermia (OAT) phenotype frequency observed within these patients [10,26,27] or only to the ICE. For this reason, other FISH studies on spermatozoa from a large number of Robertsonian, translocations carriers should be performed in order to give precise information about the genetic risks linked to those who carry structural chromosomes abnormalities.…”
Section: Discussionmentioning
confidence: 92%